On the differentiation of vector valued composite Lipschitz continuous functions - Gilliam, K. P.; Vinante, C. D. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
It is well know that there exists in economic what is referred to as “kinked” demand curves. That is, curves that are Lipschitz continuous. This paper presents a technical theorem on the existence of partial derivatives (and the applicability of the chain rule to compute them) of certain class of camposite Lipschitz continuous vector valued functions that appear in Mathematical Economics.